Analyzing Russia’s Interests in the 2020 Nagorno-Karabakh Ceasefire Agreemen - Shafira Khairunnisa Anggraeni (Jurnal Hubungan Internasional, 2022)
The Nagorno-Karabakh war has been one of the most important conflicts in the South Caucasus. The two nations involved, Azerbaijan and Armenia, have been in conflict more times than in cooperation ever since their independence from the Soviet Union. The territory disputed, Nagorno-Karabakh, has been internationally recognized as Azerbaijan’s since the United Nations General Assembly Resolution in 2008. However, this did not stop the conflict, as seen with the newest escalation happening in September of 2020. In the majority of the conflict, Russia has been a constant presence, being a mediator as well as a military supplier to both countries. Russia also has been involved in peacekeeping efforts, sending peacekeeping forces to Nagorno-Karabakh. In November 2020, a ceasefire agreement was reached involving Azerbaijan, Armenia, and Russia. This paper aims to examine Russia’s interest in its involvement in the conflict, the weaknesses of the ceasefire agreement, and Russia’s gains from the agreement and the overall situation. This paper found that Russia’s interests lay in its economic relationship with Armenia and Azerbaijan and in exercising influence in the region with the deployment of its peacekeeping contingent.